2019
DOI: 10.1002/jbmr.3830
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Abdominal Aortic Calcification, Bone Mineral Density, and Fracture in Older Women

Abstract: Although a relationship between vascular disease and osteoporosis has been recognized, its clinical importance for fracture risk evaluation remains uncertain. Abdominal aortic calcification (AAC), a recognized measure of vascular disease detected on single‐energy images performed for vertebral fracture assessment, may also identify increased osteoporosis risk. In a prospective 10‐year study of 1024 older predominantly white women (mean age 75.0 ± 2.6 years) from the Perth Longitudinal Study of Aging cohort, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 35 publications
3
40
1
2
Order By: Relevance
“…Our results are complementary to and extend the results of Lewis and colleagues, ( 15 ) who estimated the joint associations of prevalent vertebral fracture and AAC on lateral spine densitometric images with risks of incident clinical fractures and fracture‐related hospitalizations among women aged 70 years and older enrolled in the Calcium Intake Fracture Outcomes Study (CAIFOS). Unlike our study of older men, the interaction term between prevalent vertebral fracture and AAC‐24 score level was significant, indicating the association of AAC with incident clinical fracture was stronger if prevalent vertebral fracture was also present.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results are complementary to and extend the results of Lewis and colleagues, ( 15 ) who estimated the joint associations of prevalent vertebral fracture and AAC on lateral spine densitometric images with risks of incident clinical fractures and fracture‐related hospitalizations among women aged 70 years and older enrolled in the Calcium Intake Fracture Outcomes Study (CAIFOS). Unlike our study of older men, the interaction term between prevalent vertebral fracture and AAC‐24 score level was significant, indicating the association of AAC with incident clinical fracture was stronger if prevalent vertebral fracture was also present.…”
Section: Discussionsupporting
confidence: 83%
“…Only one investigation, conducted in a cohort of women aged 70 years and older, thus far has examined the joint prediction of incident fractures from ascertainment of both prevalent vertebral fracture and AAC. ( 15 ) This study found that prevalent vertebral fracture and AAC were both associated with incident clinical fracture adjusted for each other and for other traditional risk factors.…”
Section: Introductionmentioning
confidence: 69%
“…The relationship between vascular calcification and low BMD is of particular interest (98), most evident (though not exclusively) in the chronic kidney disease population. Abdominal aortic calcification is associated with lower BMD and vertebral fractures (99); and the extent to which genetic pleiotropy underpins vascular calcification [itself heritable (44)] and osteoporosis is the source of active investigation. There are also monogenic forms of vascular calcification (for example, pathogenic variants in ABCC8 causing pseudoxanthoma elasticum (MIM264800) [45][46][47]].…”
Section: Detecting High Bmd In Clinical Practicementioning
confidence: 99%
“…Vascular calcification is linked to osteoporosis and low BMD in older people or type 2 diabetes patients [ 9 , 10 ]. Older women with more marked abdominal aortic calcification (AAC) are at a higher risk of fracture [ 11 ]. From the point of basic science, arterial calcification processes share some pathways in common with bone physiology, particularly osteoporosis [ 12 ].…”
Section: Discussionmentioning
confidence: 99%